Custos e benefícios de um programa de exercício aeróbios na doença pulmonar obstrutiva crônica: ensaio cliníco aleatório controlado - Farias, Catharinne Angélica Carvalho de (2012)
Pulmonary Rehabilitation, especially due to aerobic exercise, positive impact in reducing morbidity/mortality of patients with COPD, however the economic impact with costs of implementing simple programs of aerobic exercise are scarce. This is a blind randomized clinical trials, which aimed to evaluate the costs and benefits of a simple program of aerobic exercise in individuals with COPD, considering the financial costs of the Public Health System and its secondary endpoints. We evaluated lung function, the distance walked during six minutes of walking, the respiratory and peripheral muscle strength, quality of life related to health (QLRH), body composition and level of activity of daily living (ADL) before and after eight weeks of an aerobic exercise program consisting of educational guidance for both groups, control and intervention and supervised walks to the intervention group. The health costs generated in both groups were calculated following table Brazilian Public Health System. The sample consisted of forty patients, two being excluded in the initial phase of desaturation during the walk test six minutes. Were randomized into control and intervention group thirty-eight patients, three were excluded from the control group and one was excluded from the intervention group. At the end, thirty-four COPD comprised the sample, 16 in the control group and 18 in the intervention group (FEV1: 50.9 ± 14% pred and FEV1: 56 ± 0.5% pred, respectively). After for intervention, the intervention group showed improvement in meters walked, the sensation of dyspnea and fatigue at work, BODE index (p <0.01) in QLRH, ADL level (p <0.001) as well as increased strength lower limbs (p <0.05). The final cost of the program for the intervention group was R $ 148.75, including: assessments, hiking supervised by a physiotherapist and reassessments. No patient had exacerbation of IG, while 2 patients in the CG exacerbated, generating an average individual cost of R $ 689.15. The aerobic exercises in the form of walking showed significant clinical benefits and economic feasibility of its implementation, due to low cost and easy accessibility for patients, allowing them to add their daily practice of aerobic exercises